2017
DOI: 10.5897/ijlis2016.0739
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usefulness as a correlate of extent of Information and Communications Technologies (ICTs) use for teaching by library educators in universities in Nigeria

Abstract: Information and Communications Technologies (ICTs) integration for teaching is the application of information, communication and telecommunication technologies, equipment and hardware for instructional purposes. With ICT, a lot of information resources and software can be provided on time and with ease. The research presumed that the perception of how useful for teaching (or otherwise) the ICTs are may affect their use among library educators in Nigerian universities. To establish or refute this, descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The finding that universities ICT teaching facilities insignificantly predicted e-learning implementation was contrary to the findings of previous scholars. For example Akinde and Adetimirin (2017), Asubiojo and Ajayi (2017), Eze et al (2018), Gupta et al (2022), Hailye (2020), Matviichuk et al (2022), Ouma (2021), andSemlambo et al (2022) indicated that ICT teaching facilities related to e-learning implementation. Possibly, the finding was contrary to the findings of most scholars because the facilities of the universities were not accessible to students when outside the university campus.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that universities ICT teaching facilities insignificantly predicted e-learning implementation was contrary to the findings of previous scholars. For example Akinde and Adetimirin (2017), Asubiojo and Ajayi (2017), Eze et al (2018), Gupta et al (2022), Hailye (2020), Matviichuk et al (2022), Ouma (2021), andSemlambo et al (2022) indicated that ICT teaching facilities related to e-learning implementation. Possibly, the finding was contrary to the findings of most scholars because the facilities of the universities were not accessible to students when outside the university campus.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Scholars (e.g. Akinde & Adetimirin, 2017;Asubiojo & Ajayi, 2017;Eze et al, 2018;Gupta et al, 2022;Hailye, 2020;Matviichuk et al, 2022;Ouma, 2021;Semlambo et al, 2022) have related ICT teaching facilities and e-learning implementation. The studies above revealed that ICT teaching facilities are important in the implementation of e-learning.…”
Section: Tangible Resources and Implementation Of E-learningmentioning
confidence: 99%
“…This finding is consistent with the findings of previous scholars. For instance, Akinde and Adetimirin (2017) found out that many ICTs were beneficial to teaching. Similarly, Asubiojo and Ajayi (2017) reported that that the implementation and use of ICT in Education improved the education system by enhancing teachers' instructional effectiveness.…”
Section: Discussionmentioning
confidence: 99%